CORRELATION OF IMPACTED MANDIBULAR THIRD MOLAR WITH INCIDENCE OF IPSILATERAL ANGLE AND CONDYLAR FRACTURES IN MANDIBULAR TRAUMA - Abidi, Syed Yasir Ali; Babar, Adnan; Niazi, Kaleem Ullah; Khan, Ali Akhtar; Maryam, Atiqa; Rasheed, Nazish (Pakistan Armed Forces Medical Journal, 2020)
Objective: This study aims to evaluate association of impacted lower third molars with incidence of ipsilateral mandibular angle and condylar fractures.Study design: Observational study.Place of study: Maxillofacial Surgery Department Armed Forces Institute of DentistryMaterials and methods: Patients reporting to armed forces institute of dentistry maxillofacial surgery department OPD were diagnosed on the basis of history, clinical signs and symptoms and radiological examinations were categorized as Mandibular Angle and Condylar fractures and impacted lower third molars. A total number of 234 radiographs of patients were examined.Duration of study: 01 year from 01 January 2019 to 31st December 2019.Results: Out of total sample size of 234 patients, 70% (79 patients) Mandibular angle fractures occurred with patients with impacted lower third molars (112 patients) and 65% (80 patients) mandibular condylar fractures occurred with patients without impacted lower third molars (122 patients). Statistically significant P-value was 0.000 that is